2020
DOI: 10.1371/journal.pgen.1008721
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SPATA13/ASEF2 cause primary angle closure glaucoma

Abstract: Current estimates suggest 50% of glaucoma blindness worldwide is caused by primary angle-closure glaucoma (PACG) but the causative gene is not known. We used genetic linkage and whole genome sequencing to identify Spermatogenesis Associated Protein 13, SPATA13 (NM_001166271; NP_001159743, SPATA13 isoform I), also known as ASEF2 (Adenomatous polyposis coli-stimulated guanine nucleotide exchange factor 2), as the causal gene for PACG in a large seven-generation white British family showing variable expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…As opposed to Asian populations, the prevalence of PACG is low in Europe (0.42%) and North America (0.26%) [ 25 , 126 ], and genetic data on PACG in ED is generally lacking [ 126 ]. The low prevalence makes study and identification of affected ED families difficult [ 156 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As opposed to Asian populations, the prevalence of PACG is low in Europe (0.42%) and North America (0.26%) [ 25 , 126 ], and genetic data on PACG in ED is generally lacking [ 126 ]. The low prevalence makes study and identification of affected ED families difficult [ 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in 2020, Waseem, et al conducted a study of PACG in an ED family in the UK [ 156 ]. They studied 39 blood-related patients, 5 of which were unaffected (penetrance 87.2%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another recent study using a combination of linkage and whole-genome sequencing, Waseem et al identified a causal genetic variant in SPATA13 (spermatogenesis associated protein 13) in a seven-generation PACG family of British origin. 196 A single 9bp in-frame deletion variant (c.1432_1440del; p.478_480del) in SPATA13 on chromosome 13q12.12 was found to segregate in all the affected individuals of the family with variable expression and decreased penetrance. Additional rare variants in SPATA13 were also observed in unrelated PACS, PAC or PACG cohorts, including the 9bp deletion, supporting the causal evidence of this variant.…”
Section: Next-generation Sequencing Studies In Pacgmentioning
confidence: 99%